2023
DOI: 10.1021/acs.est.3c05108
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Biogas Slurry-Derived Colloids to Plant P Uptake and Phosphatase Activities: Spatiotemporal Response

Yuxin Guo,
Yuanyuan Lu,
Kamel Mohamed Eltohamy
et al.

Abstract: The bioavailability for varied-size phosphorus (P)-binding colloids (P coll ) especially from external P sources in soil terrestrial ecosystems remains unclear. This study evaluated the differential contribution of varioussized biogas slurry (BS)-derived colloids to plant available P uptake in the rhizosphere and the corresponding patterns of phosphatase response. Keeping the same content of total P input (15 mg kg −1 ), we applied different sizefractioned BS-derived colloids including nanosized colloids (NCs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…The P coll is recognized as a particularly mobile form of P, , contributing significantly to P loss from agricultural systems , and eutrophication of freshwater bodies. , It constitutes a substantial portion of total P in agricultural systems (13%–95%) , and streams (up to 30%). , Soil P coll mobility is influenced by various physical, chemical, and biological factors, , with pH, organic carbon (OC), and elements such as Fe, aluminum (Al), Mn, and calcium (Ca) being significant. , Despite its known importance, P coll behavior under reducing (anoxic) conditions is under-researched. A prior study on grassland soils revealed the anoxia-induced release of colloid- and nanoparticle-bound P < 450 nm, influenced by Fe .…”
Section: Introductionmentioning
confidence: 99%
“…The P coll is recognized as a particularly mobile form of P, , contributing significantly to P loss from agricultural systems , and eutrophication of freshwater bodies. , It constitutes a substantial portion of total P in agricultural systems (13%–95%) , and streams (up to 30%). , Soil P coll mobility is influenced by various physical, chemical, and biological factors, , with pH, organic carbon (OC), and elements such as Fe, aluminum (Al), Mn, and calcium (Ca) being significant. , Despite its known importance, P coll behavior under reducing (anoxic) conditions is under-researched. A prior study on grassland soils revealed the anoxia-induced release of colloid- and nanoparticle-bound P < 450 nm, influenced by Fe .…”
Section: Introductionmentioning
confidence: 99%